Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Rumah Makan SSP (SPESIAL SUPER PENYET) - Riyanto, Agus, Muzakar Isa, SE, M.Si (2015)
The aim of this research is to find out the effect of service quality which contains 5 dimensions, reliability, tangibles, responsiveness, assurance, and empathy as partial, simultaneous as far as the effect of service quality toward the satisfaction of customer in SSP restaurant (special super penyet) at Menco, Kartasura. The population of this research is all customers restaurant of special super penyet (SSP) at Menco, Kartasura. The sample which is taken around 100 respondent using Accidental Sampling technique that is the technique of determining sample based on accident, whoever accidentally meet the researcher can be used as sample if the accidental people is compatible as date source. This research uses the method of bifilar regression data analysis and test-hypothesis, test-statistic t, test-statistic F, and determination coefficient. The result of this research shows the variable of reliability significantly 0.392 > 0.05 as the result reliability effected insignificantly toward the satisfaction of customers. The variable of tangibles with significance level 0.911 > 0.05 so, tangibles effected insignificantly toward the satisfaction of customers. The variable of responsiveness with the significance level 0.092 > 0.05 therefore responsiveness effected insignificantly to the customers' satisfaction. The variable of assurance with the level 0.068 > 0.05 so the effect of assurance is insignificantly toward the satisfaction of customers. The emphaty variable with the level 0.001< 0.05 so the emphaty effect is insignificantly. The result of the research showed that the significance 0.000 < 0.05 therefore reliability, responsiveness, assurance, emphaty, and tangible simultaneouslygave the effect of the satisfaction of customers. The point of adjusted R square is derived 0.650 or 65.0 % of customers' satisfaction can be explained by the variable of reliability, tangibles, responsiveness, assurance, and emphaty whereas 35.0 % is explained by the other variable which is not researched in this research. Keywords: reliability, tangibles, responsiveness, assurance, emphaty, services quality, and the satisfaction of customers.